The emergence of the SARS-CoV-2 Omicron variant - Thomson, Emma (Henry Stewart Talks, 2022)
Emergence of the Omicron variant, The genetic characteristics of the Omicron variant and the phenotypic advantages they provide, Biology and epidemiology of the Omicron variant, Immune escape and vaccine’s effectiveness, Clinical severity, Potential emergence of novel variants combining multiple mutations